Association Between Gut Dysbiosis and Sepsis-Induced Myocardial Dysfunction in Patients With Sepsis or Septic Shock - Chen, Yu; Zhang, Fu; Ye, Xin; Hu, Jing-Juan; Yang, Xiao; Yao, Lin; Zhao, Bing-Cheng; Deng, Fan; Liu, Ke-Xuan (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: Sepsis-induced myocardial dysfunction (SIMD) seriously affects the evolution and prognosis of the sepsis patient. Gut microbiota has been confirmed to play an important role in sepsis or cardiovascular disease, but the changes and roles of gut microbiota in SIMD have not been reported yet. This study aims to assess the compositions of gut microbiota in sepsis or septic patients with or without myocardial injury, and find the relationship between gut microbiota and SIMD. Methods: The prospective, observational, and 1:1 matched case-control study was conducted to observe gut microbiota profiles from patients with SIMD (n=18) and matched NSIMD patients (n=18) by 16S rRNA gene sequencing. Then the relationship between the relative abundance of microbial taxa and clinical indicators and clinical outcomes related to SIMD were analyzed. The receiver operating characteristic (ROC) curves were used to evaluate the predictive efficiencies of the varied gut microbiota to SIMD. Results: SIMD was associated with poor outcome in sepsis patients. The beta-diversity of gut microbiota were significantly different between SIMD patients and NSIMD subjects. The gut microbiota profiles in different levels were significant differed between the two groups. Additionally, the abundance of some microbes (Klebsiella_variicola, Enterobacteriaceae, and Bacteroides_vulgatus) were correlated with clinical indicators and clinical outcomes. Notably, ROC analysis indicated that Klebsiella_variicola may be a potential biomarker of SIMD. Conclusion: Our study indicates that SIMD patients may have a particular gut microbiota signature, and gut microbiota might be a potential diagnostic marker for evaluating the risk of developing SIMD.